Comparative analysis of the perceived quality by combat sports spectators - Angosto Sánchez, S.; Martínez-Abellán, A.; Rabadán Iniesta, J. C.; López-Gullón, J. M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The interest in knowing the user's perceptions regarding the quality and value of the service has been transferred to the sports events. Knowing which are the determinant elements for the general satisfaction of the spectator, will cause to the organizations a greater loyalty and improvement in its sport projects. This study analyzes, through a questionnaire, the different dimensions from the quality perceived, services quality, competitions elements and futures intentions in the prediction of the general satisfaction of the spectator in Taekwondo and Wrestling Spanish Championships. The results indicated the quality dimension was the worst valued for the spectators in both sports, being the results quality the low punctuation dimension. However, the future intentions has got the best valued dimension for the spectators, there are no exist more differences between the both championships. These results would be relevant for managers in charge of sport events in order to plan strategies dedicated to services improvement.